2008
DOI: 10.1007/s00216-007-1730-0
|View full text |Cite
|
Sign up to set email alerts
|

Surface analysis of different boundary layers on steel discs formed in a lubricated tribocontact during laboratory test compared with field application

Abstract: The aim of this study was to gain knowledge of tribological layers on a steel disc. This steel disc has been used in a transmission system in the field. ATF-oil (automatic transmission fluid), which contains different surface-adhering additives, serves as a lubricant and as a cooling fluid in the tribological system. Over time, the tribological characteristics of the system changed. Special interest in this study lies in the modifications of the steel surface. The field-used disc was therefore compared with mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Previous research indicates that the tribologically (i.e. interacting surfaces in relative motion to each other) built thin layers on the surface are formed by additives and degradation products of the additives which were present originally in the base lubricant 9, 10. It was also shown that chemical changes on the surface are primarily responsible for the tribological behavior and not topographical changes of the surface 10.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research indicates that the tribologically (i.e. interacting surfaces in relative motion to each other) built thin layers on the surface are formed by additives and degradation products of the additives which were present originally in the base lubricant 9, 10. It was also shown that chemical changes on the surface are primarily responsible for the tribological behavior and not topographical changes of the surface 10.…”
mentioning
confidence: 99%
“…interacting surfaces in relative motion to each other) built thin layers on the surface are formed by additives and degradation products of the additives which were present originally in the base lubricant 9, 10. It was also shown that chemical changes on the surface are primarily responsible for the tribological behavior and not topographical changes of the surface 10. For a better understanding of the tribosystem it is essential to enhance knowledge of the chemical composition of the lubricant and its surface layer 9–12.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Steel discs placed above and below ran against a rotating friction (pad) disc in the middle under lubricated conditions. The tribometer's configuration enables tests up to 100 rounds/min, corresponding to a mean sliding velocity of approximately 40 m/s [8]. Tests were performed in ambient air.…”
Section: Test Set-upmentioning
confidence: 99%
“…22,23 These tribolayers are generally formed by additive molecules as well as reaction products of both the additives and the base lubricant. 24 As tribolayers alter the contact surface they are the main influence on changes in friction behavior of a tribological system. Knowledge about what chemical composition of surface layers is to be expected from certain lubricants is essential for improvement of the design of both contact surfaces and the lubricant formulation.…”
Section: Introductionmentioning
confidence: 99%